Veno-Venous Extracorporeal Lung Support as a Bridge to or Through Lung Volume Reduction Surgery in Patients with Severe Hypercapnia. Issue 8 (August 2020) - Akil, Ali; Ziegeler, Stephan; Reichelt, Jan; Lavae-Mokhtari, Mahyar; Freermann, Stefan; Semik, Michael; Fichter, Joachim; Rehers, Stephanie; Dickgreber, Nicolas Johannes; Richter, Lars; Ernst, Erik Christian; Fischer, Stefan
Abstract : Extracorporeal lung support (ECLS) represents an essential support tool especially for critically ill patients undergoing thoracic surgical procedures. Lung volume reduction surgery (LVRS) is an important treatment option for end-stage lung emphysema in carefully selected patients. Here, we report the efficacy of veno-venous ECLS (VV ECLS) as a bridge to or through LVRS in patients with end-stage lung emphysema and severe hypercapnia. Between January 2016 and May 2017, 125 patients with end-stage lung emphysema undergoing LVRS were prospectively enrolled into this study. Patients with severe hypercapnia caused by chronic respiratory failure were bridged to or through LVRS with low-flow VV ECLS (65 patients, group 1). Patients with preoperative normocapnia served as a control group (60 patients, group 2). In group 1, VV ECLS was implemented preoperatively in five patients and in 60 patients intraoperatively. Extracorporeal lung support was continued postoperatively in all 65 patients. Mean length of postoperative VV ECLS support was 3 ± 1 day. The 90 day mortality rate was 7.8% in group 1 compared with 5% in group 2 ( p = 0.5). Postoperatively, a significant improvement was observed in quality of life, exercise capacity, and dyspnea symptoms in both groups. VV ECLS in patients with severe hypercapnia undergoing LVRS is an effective and well-tolerated treatment option. In particular, it increases the intraoperative safety, supports de-escalation of ventilatory strategies, and reduces the rate of postoperative complications in a cohort of patients considered "high risk" for LVRS in the current literature.